Influence of factors of soil formation in the properties of soils in Mixteca, Oaxaca, México - Figueroa Jáuregui, María de Lourdes; Martínez Menez, Mario Roberto; Ortíz Solorio, Carlos Alberto; Fernández Reynoso, Demetrio Salvador (REVISTA TERRA LATINOAMERICANA, 2018)
The soil-forming process is determined by the interaction of six soil-forming factors: climate, organisms, topography, parent material, time and soil use; the magnitude of all soil properties is determined by the action of these factors. In this work we determined the forming factors that influence the type of soil present in the rancho Dolores watershed in the Mixteca region in the state of Oaxaca, as well as the properties of these soils. An analysis of principal components and an unsupervised classification for the delimitation of soil units were carried out, in which samplings and laboratory analysis of some physical and chemical properties were carried out. The forming factors that explain the variability of the soils of the watershed were slope, topographic position index, parental material and land use. Five soil units were delimited with their spatial distribution in the watershed and associated with their properties of texture, apparent density, field capacity, permanent wilting point, saturation percent, saturated hydraulic conductivity, pH and organic matter content. There is a strong relationship between the relief parameters and the soils, reason why we recommend the study of the formation, distribution, and cartography of soils from a geomorphological point of view, as well as the analysis of vegetation.